Análise do impacto na função gonadal e erétil da captação de espermatozoides no testículo de animais submetidos a orquidopexia experimental : comparação da técnica de extração convencional com a aspirativa - Barroso, Leocácio Venicius de Sousa (2015)
The development of intracytoplasmic sperm injection (ICSI) and assisted reproductive technology was a major breakthrough in the treatment of male infertility causes. Consequently ICSI testicular biopsy is done not only to evaluate spermatogenesis, but also to capture spermatozoa. This study aims to compare the impact of conventional extraction technique with aspiration for sperm retrieval in gonadal and erectile function in rats with orquidopexy testicles. Pilot study to determine the damage caused by orchidopexy was initially performed in six rats. Then 26 rats were randomized into 4 groups: Group 1 (n = 6) - Rats intact (non-operated) underwent dosage of testosterone and the next day monitoring of intra-cavernous pressure; Group 2 (n = 7) - At first the animals were subjected to experimental orchidopexy. Fifteen days after orchidopexy, the animals were subjected to testosterone dosage and the next day the sperm retrieval. After one week period, testosterone dosed again followed by monitoring of intra-cavernous pressure the following day; Group 3 (n = 7) - Initially, the animals were subjected to experimental orchidopexy. Fifteen days after, animals were subjected to determination of testosterone and the day after subjected to testicular sperm extraction. After one week period, testosterone was dosed again and followed by monitoring of intra-cavernous pressure; Group 4 (n = 6) - testosterone was dosed at study entry and followed by orchidopexia. Fifteen days later made new dosage testosterona. On the next day we performed a sham procedure. One week later the rats were subjected to the assay of testosterone and the next day the monitoring of intra-cavernous pressure. Was considered significant P <0.05 (5%). Comparisons between groups were made with t-test, ANOVA and Tukey. Regarding the damage to spermatogenesis, 15 days orchidopexia was enough to cause testicular damage. Regarding the effect of hormone function in orchidopexic rats there was no significant difference (p = 0.4446) compared to testosterone at baseline (D0) 4.58 ± 1.44ng/ml with testosterone at the end of the experiment (D15) 4.99 ± 1.96ng/ml). There was no significant difference (p = 0.4446) comparing the serum concentration of testosterone measured in rats submitted to orchidopexy (in GROUPS 2:03) (6.66 ± 4.67ng/ml) with the animals of group 1 (not operated) (4.75 ± 1.45ng/ml). There was no impact of testosterone in animals subjected to suction and sperm orchidopexy (Group 3) (± 3.96. 0.80ng/ml) compared to non-operated animals (Group 1) (4.75 ± 1.45ng/ml) p = 0.27. Similarly, there was no significant difference (P = 0.2625) in testosterone of rats subjected to orchidopexy and aspiration Group 3 (3.96 ± 0.80ng/ml) compared with animals subjected to isolated orchidopexy Group 4 (4.99 ± 1.96ng/ml) p = 0.26. The surgical sperm retrieval did not cause hypogonadism in orquidopexics animals. Testosterone Group 2 (orchidopexy and extraction), and Group 1 animals were not operated (5.35 ± 4.65ng/ml) and (4.75 ± 1.45ng/ml), respectively, p = 0.76. There was no difference in testosterone of animals subjected to orchidopexy and extraction (5.35 ± 4.65 ng / ml) compared with animals underwent isolated orchidopexy (4.99 ± 1.96 ng / ml) p = 0.86. There was no significant difference comparing testosterone Sham Group Group 4 (3.70 ± 1.27ng/ml), rats subjected to orchidopexy and simulated operation with non-operated animals (4.75 ± 1.45ng/ml) p = 0.21. The absolute number of sperm obtained by extraction technique (41.00 ± 7.01) was significantly higher than the number of spermatozoa obtained by aspiration technique (21.33 ± 8.14) p = 0.0012. The weight of testicular tissue obtained by extraction technique (0.09 ± 0.02 g) was significantly higher than that obtained by aspiration technique (0.04 ± 0.04 g) p = 0.0452. Regarding the effect of collecting sperm in erectile function there was no significant difference comparing Groups 1 and 4 for the reason ICP/MAP (intracavernous pressure/mean arterial pressure) and for the AUC (area under the curve) in neither of the frequencies (Hz 2, 4, 6, 8, 10). There was no significant difference comparing Groups 2, 3 and 4 for the reason PIC/PAM and ASC for none of the frequencies (2, 4, 6, 8, 10Hz). In conclusion, the harvest of testicular sperm in orquidopexics rats by extraction technique or by aspiration did not change the gonadal and erectile function of the animal. The amount of sperm obtained in the extraction technique was greater than the aspiration technique.